# `y = (sin(x))^ln(x)` Use logarithmic differentiation to find the derivative of the function.

*print*Print*list*Cite

Expert Answers

hkj1385 | Certified Educator

given `y = (sinx)^(lnx)`

taking log to the base 'e' both sides we get,

`lny = lnx*(lnsinx)`

Differentiating both sides we get

`(1/y)*dy/dx = (1/x)*{lnsinx} + (cosx/sinx)*lnx`

or,

`y*dy/dx =(1/x)*{lnsinx} + (cotx)*lnx `

or, `dy/dx = y*[(1/x)*{lnsinx} + (cotx)*lnx]`

or, dy/dx = `(sinx)^(lnx)*[(1/x)*lnsinx + cotx*lnx]`

` `

` `

` `